2017
DOI: 10.1182/blood.v130.suppl_1.897.897
|View full text |Cite
|
Sign up to set email alerts
|

Final Evaluation of Randomized CML-Study IV: 10-Year Survival and Evolution of Terminal Phase

Abstract: Background Chronic myeloid leukemia (CML)-study IV was designed to explore whether treatment with imatinib (IM) at 400mg/day (n=400) could be optimized by doubling the dose (n=420), adding IFN (n=430) or cytarabine (n=158) or using IM after IFN-failure (n=128). Methods From July 2002 to March 2012, 1551 newly diagnosed patients in chronic phase were randomized into a 5-arm study. The study was powered to detect a survival difference of 5% at 5 years. The impact of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The results suggest that ZNF208 variations may have a substantial impact on the progression of HBV. The study found that ZNF208 polymorphisms significantly increased susceptibility to HBV infection (P = 0.008) [50]. Furthermore, a scientific investigation has asserted that mutations in the ZNF208 gene are associated with an inclination towards developing esophageal cancer [58].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The results suggest that ZNF208 variations may have a substantial impact on the progression of HBV. The study found that ZNF208 polymorphisms significantly increased susceptibility to HBV infection (P = 0.008) [50]. Furthermore, a scientific investigation has asserted that mutations in the ZNF208 gene are associated with an inclination towards developing esophageal cancer [58].…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between CML advancement and the development of a lethal blast crisis can be attributed to ZNF208, a member of the biologically significant group of genes known as Zinc Finger Proteins. The human genome contains a large number of zinc finger (ZNF) genes, with around 500-600 members [50]. These proteins have a role in controlling genes and the process of development, and they have remained mostly the same throughout evolution [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 10-year major MMR and MR4.5 rates were 93 and 63%, respectively, with imatinib [27]. Several studies comparing imatinib 400 vs. 800 mg failed to show the survival benefit of imatinib 800 mg over 400 mg [28][29][30]. Therefore, imatinib at a dose of 400 mg daily is recommended for treating patients with newly diagnosed CML-CP.…”
Section: Frontline Therapymentioning
confidence: 99%